2021
DOI: 10.18502/ijm.v13i3.6386
|View full text |Cite
|
Sign up to set email alerts
|

Current-proven neonatal sepsis in Indonesian tertiary neonatal intensive care unit: a hematological and microbiological profile

Abstract: Background and Objectives: Neonatal sepsis is the third leading cause of neonatal death in the world. The patterns of pathogens causing neonatal sepsis varies in many countries. This study was aimed to identify hematological and microbiological profile of culture-proven neonatal sepsis in Indonesian tertiary neonatal intensive care unit (NICU). Materials and Methods: Hospital based cross-sectional study was conducted in all inborn neonates that were suspected sepsis neonatal over a period of six months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…In the present study, it has been found that hemoglobin and the platelet Counts in the septic group were statistically significantly decreased compared with the corresponding values in the control groups of infants. These results correlated with those of two recent studies [33,34] . In such cases, the low Hb level could be explained as a result of increased hemolysis of red blood cells caused by bacterial infection in blood [34] .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, it has been found that hemoglobin and the platelet Counts in the septic group were statistically significantly decreased compared with the corresponding values in the control groups of infants. These results correlated with those of two recent studies [33,34] . In such cases, the low Hb level could be explained as a result of increased hemolysis of red blood cells caused by bacterial infection in blood [34] .…”
Section: Discussionsupporting
confidence: 93%
“…14 In another study done in Indonesian tertiary neonatal care unit it was seen of all culture positive neonates 13 (25%) in early-onset neonatal sepsis (EONS) and 39 (75%) in late-onset neonatal sepsis (LONS). 15 More incidence of EONS in our study may be explained by more preterm neonate being affected than term neonate in this study.…”
Section: Discussionmentioning
confidence: 50%
“…Penggunaan kultur darah sebagai pemeriksaan baku karena sepsis merupakan respon inflamasi sistemik terhadap infeksi sehingga dapat penegakan diagnosisnya melihat adanya bakteremia pada pasien dengan cara isolasi bakteri (27,28). Namun, sensitivitas dan spesifisitas kultur darah secara keseluruhan rendah, sebagian bergantung pada volume darah yang diambil, waktu pengambilan darah, pengobatan sebelumnya dengan antibiotik, dan keberadaan organisme yang hidup (6).…”
Section: Manifestasi Klinisunclassified